Financing conditions and toxic emissions - Martin Goetz (Goethe University Frankfurt, SAFE - Sustainable Architecture for Finance in Europe, 2019)
Exploiting heterogeneity in U.S. firms' exposure to an unconventional monetary policy shock that reduced debt financing costs, I identify the impact of financing conditions on firms' toxic emissions. I find robust evidence that lower financing costs reduce toxic emissions and boost investments in emission reduction activities, especially capital-intensive pollution control activities. The effect is stronger for firms in noncompliance with environmental regulation. Examining the ability of regaining regulatory compliance by implementing pollution control activities I find that only capital-intensive activities help firms regaining compliance. These findings underscore the impact of firms' financing conditions for emissions and the environment.
urn:nbn:de:hebis:30:3-508245
Keywords: G32; E52; Q52; Q53; 330; Toxic emissions; Financing conditions; Bond markets; Unconventional Monetary Policy